Derivation Pairs on Rings and RNGs - Ebanks Bruce (Annales Mathematicae Silesianae, 2025)
We generalize a classical result about derivation pairs on function algebras. Specifically, we describe the forms of derivation pairs on rings and rngs (non-unital rings) which are not assumed to be commutative. The proofs are based on knowledge of the solutions of the sine addition formula on a semigroup. Examples are given to illustrate the results.